Investigation of the Influence of Local Low Strength Concrete on the Bearing Capacity of Bending Reinforced Concrete Beams - A. G. Tamrazyan (Железобетонные конструкции)
Reinforced concrete beams can experience local low concrete strength under certain conditions, for example, poor construction practices can cause problems such as concrete voids, surface cavities, block cracking, surface sinks and create areas of low concrete strength. This study presents the response of flexural hinge-supported reinforced concrete beams with different local areas of low concrete strength along the span. Modified models are adopted to describe the concrete properties and an ideal elastic-plastic model is adopted for the steel properties. The beam was divided into three main parts: one sensitive to bending moment, the second sensitive to shear, and the third sensitive to bond. The variables included two types of concrete strength and one reinforcement diameter. The results show that the most critical region with low concrete strength along the span of the beam is the confluence zone near the supports, which is reflected in the ductility of the load-deflection curves. A new generalized empirical model is developed to predict the effect of bearing capacity reduction from local low-strength concrete.